A bright polarization-entangled photon pair source based on silicon photonics integration - Xin Hua; Xu Yan; Lu Xu; Ying Zhu; Min Liu; Jie Yan; Daigao Chen; Hongguang Zhang; Xi Xiao (APL Photonics)
Developing a high-quality, bright source of polarization-entangled photon pairs on CMOS-compatible integrated platforms, such as silicon or silicon nitride, remains a significant challenge. Here, a novel silicon chip-based nonlinear Sagnac interferometer, which mainly integrates a bidirectionally pumped microring resonator with a polarization-splitting rotator, was proposed to generate polarization-entangled photon pairs. By pumping the system with a pulsed laser at 1550 nm and a power of 78 μW, polarization-entangled photon pairs in the telecom C-band were produced through spontaneous four-wave mixing, achieving a state-of-the-art brightness of 1.6 × 107 pairs s−1 GHz−1 mW−2. Using an off-chip polarization analyzer, the visibility of polarization-correlation interference fringe was measured to be 96.6%. Quantum state tomography revealed a fidelity of 0.958 for the maximally entangled state produced by the source. These exceptional performance metrics, combined with the integrability of the device, make it highly suitable for advanced quantum applications, particularly in multi-user entanglement-based quantum communication networks.